ARUS BARU PERBANKAN SYARIAH DI INDONESIA: TRANSFORMASI FIQH MUAMALAH DALAM PERATURAN PERUNDANG-UNDANGAN - Lutfiyah Arifin (Jurnal Ilmu Akuntansi dan Bisnis Syariah (AKSY), 2019)
The development of the sharia financial in Indonesia increasingly rapidly, not only as an alternative options, but also serves to raise people’s welfare. The system operations different with the conventional bank, loss and profit sharing, then the regulation banking concept is a certainty that can not be compromised. The regulation used as the rests and guidelines activities sharia banking so be that is believed to the public and functional of national and state. Papers scientific this explained the things that are associated with sharia banking like: the background of the estabilishment of the sharia bank, the process of dialogue between usury and loss and profit sharing, the process of the adaptability fiqh muamalah of law in sharia banking concept.